Interrogare il testimone visuale - Burke, Peter (SocietàMutamentoPolitica, 2016)
Following on from Peter Burke “Eyewitnessing” (2001), this article considers again the potential for collaboration between historians and art historians, and presents ‘ten commandments’ to be borne in mind by historians who wish to make use of visual materials in their work.